Using genetic variations to reveal the complex relationships between vegetarianism and well-being, depressive symptoms and neuroticism - Chen, Ke; Wen, Yuan; Shu, Zhendi (Frontiers in Nutrition, 2024)
Background: The relationship between vegetarianism and mental well-being remains a debated topic in traditional observational studies. Recent studies have revealed the genetic factors in vegetarianism. We aimed to use genetic variations to explore the potential causal relationships between vegetarianism and mental well-being, offering insights from a new perspective. Methods: We conducted the inverse variance weighted approach as primary analysis to explore the bidirectional genetic associations between vegetarianism (N = 442,589) and depressive symptoms (N = 180,866), neuroticism (N= 170,910), and subjective well-being (N = 298,420). The analysis used the summary data from the largest genome-wide association studies (GWAS). We also performed sensitivity analyses to ensure the robustness of the findings, accounting for potential heterogeneity and pleiotropy. Results: Genetically predicted vegetarianism showed positive causal relationships with depressive symptoms (odds ratio [OR], 3.26; 95% confidence interval [CI], 1.03–10.31; p = 0.044) and neuroticism (OR, 6.72; 95% CI, 2.29-19.74; p = 5.31×10-4), as well as a negative causal relationship with subjective well-being (OR, 0.20; 95% CI, 0.05–0.77; p = 0.019). Additionally, depressive symptoms were found to have a causal influence on vegetarianism (OR, 1.01; 95% CI, 1.00–1.02; p = 6.87×10-3). No significant heterogeneity or pleiotropy was detected. Conclusions: Vegetarianism is causally correlated with negative mental well-being, reflected in an increased risk of depressive symptoms and neuroticism, as well as lower subjective well-being. Further research should explore the underlying mechanisms in broader populations.